COMMON CHARACTERISTICS OF PHRASEOLOGICAL UNITS EXPRESSING THE CONCEPTS OF TIME AND PLACE IN ENGLISH AND UZBEK LANGUAGES (European Journal of Interdisciplinary Research and Development, 2026)
This article presents a comparative analysis of phraseological units (PUs) that conceptualize “Time” and “Place” in the English and Uzbek languages. By examining the semantic structures and cultural idioms of both languages, the study identifies universal cognitive patterns and language-specific nuances. The research highlights how both cultures utilize anthropomorphism and spatial metaphors to perceive temporal flow. The findings suggest that while spatial PUs often overlap due to physical reality, temporal PUs diverge based on historical and agricultural traditions.